Neonatal head injuries: A prospective Paediatric Research in Emergency Departments International Collaborative cohort study. (23rd December 2019) - Eapen, Nitaa; Borland, Meredith L; Phillips, Natalie; Kochar, Amit; Dalton, Sarah; Cheek, John A; Gilhotra, Yuri; Neutze, Jocelyn; Lyttle, Mark D; Donath, Susan; Crowe, Louise; Dalziel, Stuart R; et al.
Abstract : Aim: To characterise the causes, clinical characteristics and short‐term outcomes of neonates who presented to paediatric emergency departments with a head injury. Methods: Secondary analysis of a prospective data set of paediatric head injuries at 10 emergency departments in Australia and New Zealand. Patients without neuroimaging were followed up by telephone call. We extracted epidemiological information, clinical findings and outcomes in neonates (≤28 days). Results: Of 20 137 children with head injuries, 93 (0.5%) occurred in neonates. These were mostly fall‐related (75.2%), commonly from a care giver's arms, or due to being accidentally struck by a person/object (20.4%). There were three cases of non‐accidental head injuries (3.2%). Most neonates were asymptomatic (67.7%) and many had no findings on examination (47.3%). Most neonates had a Glasgow Coma Scale 15 (89.2%) or 14 (7.5%). A total of 15.1% presented with vomiting and 5.4% were abnormally drowsy. None had experienced a loss of consciousness. The most common findings on examination were scalp haematoma (28.0%) and possible palpable skull fracture (6.5%); 8.6% underwent computed tomography brain scan and 4.3% received an ultrasound. Five of eight computed tomography scan (5.4% of neonates overall) showed traumatic brain injury and two of four (2.2% overall) had traumatic brain injury on ultrasound. Thirty‐seven percent were admitted, one patient was intubated and none had neurosurgery or died. Conclusions: Neonatal head injuries are rare with a mostly benign short‐term outcome and are appropriate for observation. However, non‐accidental injuries need to be considered.